Life after google eaudiobook The fall of big data and the rise of the blockchain economy. - Gilder, George (Tantor Media, 2018)
You can say goodbye to today's Internet, New York Times bestselling author George Gilder says. Soon the current model of aggregated free content populated with "value-subtracted" advertising will die a natural death, due, of course, to the simple fact that absolutely no one wants to see online advertising. What will tomorrow's Internet look like? In Life After Google , Gilder takes listeners on a brilliant, rocketing journey into the very near-future, into an Internet with a new "bitcoin-bitgold" transaction layer that will replace spam with seamless micro-payments and provide an all-new standard for global money.